COMMUNITY EMPOWERMENT ACCELERATION MODEL TO INCREASE THE ROLE OF MICRO WAQF BANK AULIA CENDEKIA IN SHARIA ECONOMIC DEVELOPMENT - Amin, Arif Rahman Nurul; Ibrahim, Duski; Abdullah, Bukhori (istinbath, 2023)
Micro Waqf Bank is an intermediary institution that has enormous potential to increase Islamic economic development through financing accompanied by business assistance. The purpose of this study is to analyze the implementation of Micro Waqf Banks in Aulia Cendekia and formulate a model for accelerating empowerment in improving economic development. This study used a descriptive qualitative approach, data were obtained from observation and interviews, and analytical techniques used triangulation. The results of this study found that the Micro Waqf Bank in Aulia Cendekia not only offers capital loans but seeks to empower people who become customers from the beginning to become potential customers until after becoming customers, namely facilities in the form of socialization, training, Compulsory Group Training, to weekly Group activities commonly called HALMI. The impact of implementation of the empowerment acceleration model of Micro Waqf Bank Aulia Cendikia has a positive impact on customers from a shared responsibility system, without collateral or interest resulting in usury, there are no other costs that reduce customer profits. In addition, Micro  Waqf Banks are also carried out to empower the community under the supervision of OJK through accountability of internal reports to avoid actions outside the objectives and functions of  Micro Waqf Banks as a means of empowering communities in micro businesses to achieve sharia economic development